Correction: Nanoporous hybrid CuO/ZnO/carbon papers used as ultrasensitive non-enzymatic electrochemical sensors. Issue 48 (7th September 2021) - Zhang, Minwei; Zhang, Wenrui; Chen, Fei; Hou, Chengyi; Halder, Arnab; Chi, Qijin
Abstract : Correction for 'Nanoporous hybrid CuO/ZnO/carbon papers used as ultrasensitive non-enzymatic electrochemical sensors' by Minwei Zhang et al., RSC Adv., 2019, 9, 41886–41892. DOI: ; 10.1039/C9RA08223A .